THE EFFECT OF GUIDED INQUIRY LEARNING MODELS TO IMPROVE LEARNING OUTCOMES AND STUDENTS ACTIVITY LEARNING - Irma Sari Minalta Tarigan; Rita Juliani; Juli Limbong (Universitas Negeri Medan, 2018)
The aim of study is to determine the effect of Guided Inquiry learning to learning outcomes and students activity learning on Work and Energy material. Research type is quasi experiment and using Control Group Pretest-Posttesr Design method. Research conducted at SMA Swasta katolik Budi Murni 2 Medan in academic year 2016/2017. The population in this research is all students of Class X. The sample of the research is taken with class random sampling technique. In the study, the measurements in the form of pretest to the subject and then treated with Guided Inquiry Models and within a certain time post-test is given. The result of data analysis using t one party test shows that there are significant effect of guided inquiry learning to learning outcomes students on Work and Energy material.